Industry focused versus conglomerate venture capital in emerging markets of Africa - Ntshobane, Yolanda (My University, 2016)
Venture Capital (VC) is a financial intermediation that is specifically well suited to finance and support the establishment and development of fledgling entrepreneurial enterprises. This industry is a need for the private sector, and it is the right fit type of PE platform for Africa’s developing economies. However, VC development in Africa is still immature and needs the correct strategies to succeed. Decisions that have to do with venture capital stages, products (industries), and geographical scope of investments, constitute some of the fundamental elements of the venture capital industry’s overall strategy. This has to do with whether VCs and angel investors specialize or diversify their investments according industry, stages and geography. This study is designed to investigate whether the investors in the venture capital industry focus on specific industries, regions, stage of venture development or they diversify their investments throughout these categories, in the emerging markets of Africa. Both primary data and systematic review of literature was used to determine what the participants of the market prefer and the reasons for their preferences. Interviews, questionnaires and secondary data were used to gain understanding of the preferences of individual investors and venture capital firms (VCFs). As much as the data collected was not enough due to the nature of the VC industry, the indication was that the VCFs in Africa do not specifically pursue an industry or stage. But when it comes to geographic areas they prefer the enterprises closer to them. However, the international VCFs that invest in Africa are very specific in terms of what industries, stages and geographical areas to pursue. In conclusion, there is still a lot that needs to be done in Africa, especially in making information available so that further studies can be done to understand and expand this exciting industry.
Submitted to: Wits Business School University of Witwatersrand Johannesburg, South Africa Master in Finance and Investment (2016)